Circulating 27-Hydroxycholesterol and Breast Cancer Risk: Results From the EPIC-Heidelberg Cohort. (16th July 2018) - Lu, Da-Lin; Le Cornet, Charlotte; Sookthai, Disorn; Johnson, Theron S; Kaaks, Rudolf; Fortner, Renée T
Abstract: Background: 27-hydroxycholesterol (27HC) was the first identified endogenous selective estrogen receptor modulator (SERM); 27HC promoted growth and metastasis in experimental models of estrogen receptor–positive mammary cancer. There are no data on prediagnosis circulating 27HC and breast cancer risk in women. Methods: We conducted a nested case–control study in the well-characterized Heidelberg, Germany, cohort of the European Investigation into Cancer and Nutrition (EPIC) including 530 incident invasive breast cancer cases, each matched to up to two control participants (n = 1036). Serum 27HC was analyzed by liquid chromatography–mass spectrometry (LC-MS) in blood samples collected at study recruitment. Multivariable conditional logistic regression models were used to quantify the association between circulating 27HC and breast cancer risk overall, by tumor hormone receptor status (ie estrogen and progesterone receptors), and by menopausal status at blood collection. All statistical tests were two-sided. Results: 27HC was not associated with breast cancer risk overall (relative risk [RR]Quartile4vsQuartile1 [Q4vsQ1] = 0.90, 95% confidence interval [CI] = 0.66 to 1.22). The association between 27HC and breast cancer risk differed by menopausal status at blood collection ( P het = .02), but not by age at diagnosis ( P het = .78). Among women who were postmenopausal at blood collection, higher serum 27HC levels were associated with lower breast cancer risk (RRQ4vsQ1 = 0.56, 95% CI = 0.36 to 0.87). We observed no association between 27HC and breast cancer risk (RRQ4vsQ1 = 1.33, 95% CI = 0.75 to 2.38) among women who were premenopausal at blood collection. Conclusions: In this first prospective study, higher circulating 27HC was associated with lower risk of breast cancer in postmenopausal women. Identification of the first endogenous SERM associated with reduced risk of invasive breast cancer in postmenopausal women may offer novel avenues for breast cancer prevention strategies.